Perinatal and cardiac outcomes of women with hypertrophic cardiomyopathy. (12th December 2022) - L'Écuyer, Émilie; Codsi, Elisabeth; Mongeon, François-Pierre; Dore, Annie; Morin, Francine; Leduc, Line
Abstract: Rationale: Pregnancy causes important physiologic stress for women with hypertrophic cardiomyopathy. Data regarding the impact of this condition on obstetrical outcomes is missing. Objectives: Our objective was to report obstetrical and cardiac outcomes in pregnant women with hypertrophic cardiomyopathy and to assess the possible adverse effects of left ventricular outflow tract obstruction in pregnancy. Study design: This was a retrospective cohort study of pregnant women diagnosed with HCM and followed at single tertiary center between 1995 and 2019. Demographic, medical and surgical data, echocardiographic parameters, and pregnancy outcomes were abstracted through extensive chart review. Patients were divided into 2 groups: obstructive (maximal left ventricular outflow tract gradient over 30 mmHg) versus non-obstructive hypertrophic cardiomyopathy. Outcomes between groups were compared with t -test, Mann-Whitney and Fisher's exact tests when appropriate. Results: Eighteen women with 27 pregnancies were included. The study population was formed of 18 women with a total of 27 pregnancies that reached at least 20 weeks of gestation: 12 pregnancies in women with obstructive hypertrophic cardiomyopathy and 15 pregnancies in women with non-obstructive hypertrophic cardiomyopathy. Among the non-obstructive hypertrophic cardiomyopathy, 5 of them had been treated for their obstruction. One patient with obstructive hypertrophic cardiomyopathy had a medical termination of pregnancy for uncontrolled arrhythmia at 21 weeks. There were no maternal deaths. Left ventricular outflow tract obstruction was associated with increased cardiac events including arrhythmias and heart failure (5/12 versus 0/15; p  = .006). Preterm birth occurred in more than 50% of cases, resulting from induced delivery for a maternal (40%) or fetal reason (60%). Most deliveries were late preterm between 34 and 36 6/7 weeks. In both groups, birthweight was mainly distributed below the 50th percentile (89%) and 35% of neonates were born small for gestational age defined as a birthweight below the 10th percentile. Most severe cases of small for gestational age (birthweight under the 5th percentile) were found in patients with treated obstructive hypertrophic cardiomyopathy. Conclusion: Hypertrophic cardiomyopathy is associated with prematurity and small for gestational age. Left ventricular outflow tract obstruction is associated with adverse cardiac events including arrythmias or heart failure. Treated obstructive cardiomyopathy constitutes a sub-group of patients at high risk of severe small for gestational age and deserves a close surveillance. Therefore, fetal growth surveillance with ultrasound, early in the third trimester and doppler studies to assess the utero-placental perfusion in the second and third trimesters are warranted in all patients with hypertrophic cardiomyopathy regardless of the severity of their condition.